Do Off-Label Drug Practices Argue Against FDA Efficacy Requirements? A Critical Analysis of Physicians' Argumentation for Initial Efficacy Requirements. - Klein, Daniel B.; Tabarrok, Alexander (American Journal of Economics & Sociology, 2008)
The amended Food, Drug and Cosmetics Act requires efficacy certification for a drug's initial uses (“on-label”), but does not require certification before physicians may prescribe the drug for subsequent uses (“off-label”). Does it make sense to require FDA efficacy certification for new drugs but not for new uses of old drugs? Using a sequential online survey, we carried on a “Virtual conversation” with some 500 physicians. The survey asked whether efficacy requirements should be imposed on off-label uses; almost all physicians said no. It asked whether the efficacy requirements for initial uses should be dropped, and most physicians said no. We then asked respondents whether opposing efficacy requirements in one case but not the other involved an inconsistency. In response, we received hundreds of written commentaries. We organize and discuss these commentaries with an eye to understanding how the medical market certifies off-label drug uses and how this compares to FDA certification. Does off-label medicine use suggest that efficacy requirements should be placed on new uses of old drugs? Does it suggest that efficacy requirements on new drugs should be lifted? We explore these questions, and ask whether the response of many of the doctors exhibits the familiar behavior bias toward the Status quo. Reprinted by permission of the publisher.